Direct oxidative esterification of toluene with 1, 3‐dicarbonyl compounds catalysed by copper complex supported on magnetic nanoparticles. (17th November 2016) - Azizi, Kobra; Esfandiary, Naghmeh; Karimi, Meghdad; Kazemi, Maryam; Heydari, Akbar
Abstract : Toluene oxidation is one of the substantial industrial technologies since oxidized products are industrially very important intermediates. A Fe3 O4 @cysteine@Cu‐catalysed reaction that uses tert ‐butyl hydroperoxide as oxidant to produce esters from toluene and β‐diketones or β‐keto esters, enolate precursors, has been developed. Oxidative esterification of toluene with 1, 3‐dicarbonyl derivatives led to C─O bond formation and direct C─H functionalization. Abstract : C─O bond formation and direct C─H functionalization were realized using oxidative esterification of toluene with 1, 3‐dicarbonyl derivatives.